Development of augmented reality applications for school textbooks - Kulishova, N. (Українська академія друкарства, 2018)
The augmented reality (AR) is a new technology that integrates a virtual 3D model into the real world through tracking and positioning. This technology became an extremely effective tool in education: it al-lows successfully combining such advantages of printed textbooks and computer technologies as information capacity, mobility, visibility and animation capability.
Keywords: augmented reality (AR)